WHEN THE HOME BECOME A BATTLEFIELD - FEMICIDE AND THE NATIONAL SECURITY OF THE REPUBLIC OF SERBIA - Topalović, Milica; Kolarski, Ljiljana (The Policy of National Security, 2024)
Femicide, as the most extreme form of gender-based violence, has been highlighted as a special social and security problem in the Republic of Serbia in recent years. Statistical data support the fact that over a ten-year period, more than three hundred women were killed by members of households of the opposite sex, of which over a hundred were killed by the use of firearms. Although the National Security Strategy of the Republic of Serbia does not specifically recognize the phenomenon of femicide as a challenge, risk, or threat to national security, an interpretive approach can relativize this claim for at least two reasons. The first stems from the importance that the Strategy places on human security, i.e. preservation and health security of groups and individuals, where and how femicide can be included. The second stems from the importance of social policy for national security, where special attention is paid to increasing the birth rate, demographic structure, and protection of the family, which, in the context of femicide, becomes a battlefield, not a refuge. Through a semiotic analysis of the content of strategic documents, with the use of quantitative data on femicide in Serbia, the paper aims to overcome the perception of femicide as a security problem, that is, to present men's directed desire to injure, destroy or punish women as a threat to national security. A special part of the paper will be devoted to the positive correlation between the availability of firearms and the rate of femicide in the Republic of Serbia, as well as a comparative analysis of statistics and experiences of other countries that record an infamous trend of increasing the number of femicides.
Keywords: femicide; national security; security challenges; risks and threats; family-partner relation; firearms; gender-based violence